Diagnoza postępów w zakresie opanowania podstawowych umiejętności szkolnych uczennicy z umiarkowanym stopniem niepełnosprawności intelektualnej - SIKORSKI, JACEK (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Jacek Sikorski, Diagnoza postępów w zakresie opanowania podstawowych umiejętności szkolnych uczennicy z umiarkowanym stopniem niepełnosprawności intelektualnej [The assessment of progress in acquiring the basic school skills by the student with a moderate intellectual disability]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 323-338. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.18 The following article takes up the issue of assessing intellectual disability from the interdisciplinary, especially psycho-pedagogical, point of view. It pays special attention to the moderate intellectually disabled students and the difficulties which they have in acquiring such basic school skills as reading, writing and counting. However, the main aim of the research was to show all the changes (progress) in the above-mentioned basic school skills in reference to the observed student with a moderate intellectual disability, which have occurred during the 10 months’ time as a result of applying both educational and therapeutic actions and an attempt to indicate the school’s education opportunities based on the results of the research and teacher’s opinions.